ANALYSIS OF PANCASILA-BASED MORAL EDUCATION VALUES IN THE LITERACY COMIC “BAHAGIANYA SALING MEMAAFKAN” - Salsabila Laili Ramadhanti; Intan Mauliana Alifia Putri; Zudan Rosyidi (Institut Pendidikan Indonesia, 2024)
This study aims to analyze the moral education values contained in the literacy comic “Bahagianya Saling Memaafkan”. This comic combines visual appeal with a compelling narrative to effectively deliver moral messages. The research employs a library research method and content analysis to explore moral themes in the story and illustrations. The findings reveal that the comic encapsulates moral education values, including sincerity, affection, empathy, self-control, and social harmony. These values are conveyed through a family-centered narrative that resonates with local culture and illustrations that visually reinforce moral messages. The comic is relevant to moral education in Indonesia as it reflects Pancasila values, such as humanity and social justice. Additionally, it serves as an innovative and engaging learning medium to boost youth literacy and reading interest. With its attractive format and educational content, this comic supports not only theoretical moral teaching but also facilitates readers in internalizing these values into their daily lives.